Boric acid and molybdenum trioxide synergistically stimulate osteogenic differentiation of human bone marrow-derived mesenchymal stromal cells - Scheurle, Andreas; Kunisch, Elke; Boccaccini, Aldo R.; Walker, Tilman; Renkawitz, Tobias; Westhauser, Fabian (Journal of trace elements in medicine and biology, 2024)
Introduction - Metals and their metal ions have been shown to exhibit certain biological functions that make them attractive for use in biomaterials, for example in bone tissue engineering (BTE) applications. Recent data shows that Molybdenum (Mo) is a potent inducer of osteogenic differentiation in human bone marrow-derived mesenchymal stromal cells (BMSCs). On the other hand, while boron (B) has been shown to enhance vascularization in BTE applications, its impact on osteogenic differentiation is volatile: while improved osteogenic differentiation has been described, other data show that B might slow down osteogenic differentiation or reduce the calcification of the extracellular matrix (ECM) when applied in higher doses. Still, the combination of pro-osteogenic Mo and pro-angiogenic B is certainly attractive in the context of biomaterials intended for the use in BTE. - Methods - Therefore, the combined effect of molybdenum trioxide and boric acid at different ratios was investigated in this study to evaluate the effects on the viability, proliferation, osteogenic differentiation, ECM production and maturation of BMSCs. - Results - Mo ions proved to be stronger osteoinductive compared to B, in fact, while some osteogenic differentiation markers were downregulated in the presence of B, the presence of Mo provided compensation. The combined application of B and Mo indicated a combination of individual effects, partially even enhancing the expected combined performance of the single stimulations. - Conclusions - The combination of B and Mo might be beneficial for BTE applications since the limited osteogenic properties of B can be compensated by Mo. Furthermore, since B is known to be pro-angiogenic, the combination of both substances may synergistically lead to improved vascularization and bone regeneration. Future studies should assess the angiogenic performance of this combination in greater detail.